Dimensões da comunicação organizacional : emoção, afeto e afetividade nos vídeos institucionais da Panvel e do Zaffari - Castilhos, Letícia de (2016)
With the overload of information, news and prominent stimuli since the Information Era (CASTELLS, 1999), communicating with different public in an effective way has been a constant challenge to organizations and its brands. Communication that before was strictly based in the transmission and presentation of products and services, now, specially fostered by electronic means, it is directed to the relation and possible strings strengthening identity, image and organizational reputation. In this perspective, we realize one of the approximation strategies is the one called branded content – diverse content formats generated by the brand ([BARWINSKI, 2014]) which main goal is to connect emotionally companies and consumers ([TROIANO, 2014]). In this process, there may be present three dimensions of organizational communication: communicated, communicant and spoken organization (BALDISSERA, 2009). Due to such context, we decided to go with multiple case study (YIN, 2001) through appreciation and analysis of institutional videos from the companies Panvel and Zaffari, in which both companies talk about themselves using emotion, affection and affectivity, without mentioning their products and services. In this sense, the present study aims to discuss the relation of narratives and intentions in the videos in all three dimensions of organizational communication (BALDISSERA, 2009). In order to do that, we grounded the study in theoretical frames on communication (KUNSCH, 2003), organizational communication (BALDISERA, 2009), brand (PEROTTO, 2007) and emotions, affection and affectivity (SODRÉ, 2006; ROBERTS, 2005). Depth Hermeneutics (DH) (THOMPSON, 2009) is formed within the method option and five characteristics of the symbolic forms proposed by the author – intentional, conventional, structural, referential and contextual – are the base for the description and interpretation of videos. Reinterpretation, in its turn, crosses the analysis with the approached theoretical referential, mainly regarding the dimensions of organizational communication (BALDISSERA, 2009).